2005
DOI: 10.1111/j.1440-1584.2005.00710.x
|View full text |Cite
|
Sign up to set email alerts
|

Strongyloidiasis: A review of the evidence for Australian practitioners

Abstract: There is a high prevalence in many Aboriginal communities. Strongyloides infection should be excluded prior to commencing immunosuppressive therapies in patients from endemic areas. Further studies examining the public health impact of strongyloidiasis, the role of the enzyme-linked immuno-sorbent assay serological test and population-based approaches to management of the disease in endemically infected Australian populations are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
73
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(78 citation statements)
references
References 44 publications
1
73
0
1
Order By: Relevance
“…Hyperinfection by Strongyloides stercoralis is mainly seen amongst immunocompromised individuals with a high case fatality rate of around 60%. (19)(20)(21) The mortality rate of the patients having hyperinfection of the present study was 33.3%. This is characterized by an acceleration of the normal life cycle of Strongyloides stercoralis that increases its burden either in the skin or lungs or gastrointestinal tract.…”
Section: Discussionmentioning
confidence: 79%
“…Hyperinfection by Strongyloides stercoralis is mainly seen amongst immunocompromised individuals with a high case fatality rate of around 60%. (19)(20)(21) The mortality rate of the patients having hyperinfection of the present study was 33.3%. This is characterized by an acceleration of the normal life cycle of Strongyloides stercoralis that increases its burden either in the skin or lungs or gastrointestinal tract.…”
Section: Discussionmentioning
confidence: 79%
“…Most (28,32,37,38,43,46) reported a decline in antibody titer within 6 to 12 months. However, results are heterogeneous and difficult to compare due to variable and nonstandardized laboratory techniques and follow-up timings (26).…”
Section: Discussionmentioning
confidence: 99%
“…Most studies have evaluated the accuracy of ELISA, with reported sensitivities ranging from 80% to 97% and specificities ranging from 29% to 99% (9,13,17,26,33,36,55,58), while little data are available on the IFAT (22,33). The IFAT is technically more complex than ELISA and requires skillful personnel both for antigen preparation and for reading.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Extension into temperate regions has also been reported, including pockets of endemicity in the southeastern United States (2,3). Given its wide geographical distribution, S. stercoralis has been estimated to infect as many as 100 million people worldwide and is therefore an important infection to consider in patients who either reside in or have traveled to regions that are endemic for strongyloidiasis (4,5).…”
mentioning
confidence: 99%